New educational demands in industrial engineering driven by automation in the digital age (Journal SCIENCEVOLUTION, 2024)
In today's world presided by emerging technologies such as automation, artificial intelligence (AI), robotics, internet of things (IOT), big data and augmented reality; higher education is going through a period of imminent transformation. Therefore, this article provides a detailed literature review on the new educational demands for the industrial engineering career. By applying a qualitative methodological approach, bibliographic and documentary in nature, the selection and evaluation of 36 contemporary academic sources were conducted, identifying educational approaches, curricular challenges, pedagogical innovations and technical and soft skills relevant to Industry 4.0.As a result of the study, tho include the teaching of these new skills, with innovative methodologies such as project-based learning, simulations and the use of augmented reality. Also, the leading role that universities must play is noted, first overcoming pre-existing challenges, such as resistance to change, infrastructure gaps, curricular updating and that of their teaching staff. In addition, by enhancing their training capabilities with the use of AI for teaching. Finally, by creating a collaborative network between universities and with industry, so as to ensure the quality and cutting edge of educational programs.
Keywords: Automation; Industrial engineering; Digital age; Higher education